Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5811/westjem.2012.4.11600
|View full text |Cite
|
Sign up to set email alerts
|

How Frequently are "Classic" Drug-Seeing Behaviors used by Drug-Seeking Patients in the Emergency Department?

Abstract: Introduction:Drug-seeking behavior (DSB) in the emergency department (ED) is a very common problem, yet there has been little quantitative study to date of such behavior. The goal of this study was to assess the frequency with which drug seeking patients in the ED use classic drug seeking behaviors to obtain prescription medication.Methods:We performed a retrospective chart review on patients in an ED case management program for DSB. We reviewed all visits by patients in the program that occurred during a 1-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
(21 reference statements)
0
26
0
Order By: Relevance
“…They suggest that ED providers need better ways of identifying patients attempting to obtain narcotics for non-therapeutic reasons (Grover, Elder, et al, 2012). The authors conclude that 'drug-seeking patients appear to exhibit 'classically' described drug-seeking behaviors relatively infrequently' (p. 418).…”
Section: (P 262)mentioning
confidence: 99%
See 1 more Smart Citation
“…They suggest that ED providers need better ways of identifying patients attempting to obtain narcotics for non-therapeutic reasons (Grover, Elder, et al, 2012). The authors conclude that 'drug-seeking patients appear to exhibit 'classically' described drug-seeking behaviors relatively infrequently' (p. 418).…”
Section: (P 262)mentioning
confidence: 99%
“…The authors conclude that 'drug-seeking patients appear to exhibit 'classically' described drug-seeking behaviors relatively infrequently' (p. 418). They suggest that ED providers need better ways of identifying patients attempting to obtain narcotics for non-therapeutic reasons (Grover, Elder, et al, 2012).…”
Section: (P 16)mentioning
confidence: 99%
“…4,6,17 Extant analyses also are largely limited to case or cohort studies, 18 self-reports of identified heavy users, 6 and analysis of records. 19 As a result, our knowledge of pharmaceutical diversion may be overly reliant on the experiences of heavy users, and little is known about those involved in physician deception who avoid medical or legal repercussions.…”
mentioning
confidence: 99%
“…[12] Additional factors that may infl uence the provider's risk perception of perpetuating opioid misuse include insuffi cient time to assess prescription history and fear of being manipulated by the patient. Interestingly, Grover et al [13] reported that providers face diffi culty in determining patients' motives, and this uncertainty impacts appropriate analgesia. We suspect that such barriers to adequate pain management may account for the perception among our EM providers that changing their prescribing behavior would not mitigate prescription opioid misuse.…”
Section: Discussionmentioning
confidence: 99%